Regulation of education implementation in Kutai Kartanegara based on education policy - H. Hairan; A. Aini; B. Susilo (Law and Safety)
This study examines the legal and regulatory framework that governs the implementation of education in Kutai Kartanegara through education policy. The regency of Kutai Kartanegara, in this case the Regional Government, has implemented various policies in the field of education in Kutai Kartanegara. The research method used in this study is an empirical juridical legal methodology, namely a research method that uses legislative provisions related to research and field research on education implementation policy in Kutai Kartanegara Regency. The results of the study show that the implementation of education policy in the Kutai Kartanegara Regency is carried out in accordance with the powers granted by Law No. 23 of 2014 on Regional Governance. The provision of education is carried out as a mandatory concurrent matter and basic service. This is based on Article 12 paragraph (1) letter a, Law Number 23 of 2014 concerning Regional Government. The implementation of education requires a budget that is used for activities in the context of increasing Human Resources, in line with the mandate set out in Article 31, paragraph (4) of the 1945 Constitution, which states that the State shall give priority to the education budget of not less than twenty per cent of the State revenue and expenditure budget, as well as regional revenue and expenditure budgets, to meet the needs of national education. The Education Policy in Kutai Kartanegara, in this case, is based on the Kutai Kartanegara Regency Government’s commitment to increasing human resources through education, especially formal education, which seeks to determine the education budget allocation of 20 % of the Regional Revenue and Expenditure Budget (APBD).